Burundi : Poverty Reduction Strategy Paper II. (IMF Staff Country Reports; Country Report ;, 2012)
The Poverty Reduction Strategy Paper II (PRSP-II) examines the major development challenges faced by Burundi. The paper identifies achievements in areas such as security and governance, but draws attention to the below-par performance in overall economic growth and development. The primary reasons for the lack of development have been cited in the report. The four major strategic pillars of the PRSP-II provide a road-map for achieving the goals and objectives enunciated to put Burundi on the path toward sustainable development.